(Method of Separation of Acetone-Butanol-Ethanol from Fermentation Broth By Fractional Distillation) - Moestafa, Achmad; Gumbira saâ€™id, E; Suparno, Sri Wuri Handono; Sukarno, Lalu (Warta Industri Hasil Pertanian, 1996)
Acetone-butanol-etanol (ABE) mixture in fermentation broth drived from fermentation of empty bunch of palm fruit is still containing butyric and acetic acid.The mixture can be separated by into its components byfractional distillation based on their different boilling points.The presence of butyric and acetic acid in the broth liquid did not interfere the yield of distillation. It was beneficial to concentrate the ABE content before the real fractional distillation was taken place.By collecting 12% of the liquid through a simple distillation had increased the concentration of ABE mixture from 17.42 to 125.25g/1.Fractionation of concentrated ABE mixture at 45 to 65 degree C on 3:1 reflux ratio produced aceton with concentration 554.63 g/1 and purity 70.22% while those of etanol at 78 to 81 C onÂ  30:1 reflux ratio produced 424.73 g/1 and purity 53.61%.The residue was consist of water and and water was distilled like a stem distillation,since butanol has higher boiling point than water and the distillate was separated base on their different density.The yield of butanol 709.15 g/1 and purity 87.57%.